Copper-Catalyzed C(sp3)–H Azidation of 1,3-Dihydro-2H-indol-2-ones Under Mild Conditions - Bao, Wen-Hui; Gao, Le-Han; Ying, Wei-Wei; Chen, Wei-Ting; Chen, Gan-Ping; Wei, Wen-Ting; Liu, Yan-Yun; Li, Qiang (Synlett, 2019)
A simple and economical synthesis of 3-substituted 3-azido-1,3-dihydro-2H-indol-2-ones has been realized under mild conditions through copper-catalyzed C(sp3)–H azidation of the corresponding 1,3-dihydro-2H-indol-2-ones with trimethylsilyl azide. The reaction proceeds by an efficient pathway involving the addition of a N3 radical to the enol tautomer and consecutive C(sp3)−N bond formations. The method is valuable because of its mild reaction conditions, short reaction times, and broad substrate scope, and because of the rich biological activity of the resulting 3-substituted 3-azido-1,3-dihydro-2H-indol-2-one products.
Keywords: copper catalysis; radical reaction; azidoindolinones; indolinones; azidation; trimethylsilyl azide